Social representations about professional and technological education: a comparative study between entering and graduating students from integrated high school (Revista Contexto & Educação, 2022)
The study aimed to analyze the social representations about Professional and Technological Education from the perspective of students entering and graduating from Integrated High School. In order to handle such an onslaught, we rely on the theoretical foundations of the EPT, on the Theory of Social Representations, by Serge Moscovici (1961) and on the Theory of the Central Nucleus, proposed by Jean-Claude Abric (1976). A total of 113 Integrated High School students participated in the study, of these, 53 freshmen and 60 graduating students. In the methodological procedures, we took as a unit of analysis the words evoked by the students from the inducing term “Professional and Technological Education”. For data analysis, we used the software Ensemble de Programs Permettant l'Analyse des Evocations (EVOC), with a qualitative-quantitative research approach. The research results show that students entering and graduating from Integrated High School have different social representations about Professional and Technological Education and at the same time not so close to what is advocated in the conceptual bases of Professional and Technological Education.
Keywords: Social representations; Students of Integrated High School; Professional and Technological Education